2010
DOI: 10.2146/ajhp090505
|View full text |Cite
|
Sign up to set email alerts
|

Physical compatibility of 4% sodium citrate with selected antimicrobial agents

Abstract: No evidence of incompatibility was observed when vancomycin 5 mg/ mL, vancomycin 10 mg/mL, daptomycin 5 mg/mL, gentamicin 2.4 mg/mL, tobramycin 2.4 mg/mL, or linezolid 1 mg/mL was mixed with 4% sodium citrate as might occur in an antimicrobial lock. Vancomycin 20 mg/mL mixed with 4% sodium citrate displayed spectrophotometric evidence of incompatibility.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 7 publications
1
25
0
Order By: Relevance
“…Tobramycin 2.4 mg/mL and TSC 40 mg/mL display visual compatibility at room temperature and at 37 °C for 48 hours. 7 Other studies have found tobramycin 5 mg/mL plus heparin sodium 5000 units/mL or TPA 1 mg/mL to be compatible for 12 hours at room temperature. [30][31][32] Although limited, compatibility data on tobramycin with TSC or TPA support the possibility of using those agents in combination for patients intolerant of other agents or patients requiring TPA for CVC patency.…”
Section: Antibacterialsmentioning
confidence: 96%
See 2 more Smart Citations
“…Tobramycin 2.4 mg/mL and TSC 40 mg/mL display visual compatibility at room temperature and at 37 °C for 48 hours. 7 Other studies have found tobramycin 5 mg/mL plus heparin sodium 5000 units/mL or TPA 1 mg/mL to be compatible for 12 hours at room temperature. [30][31][32] Although limited, compatibility data on tobramycin with TSC or TPA support the possibility of using those agents in combination for patients intolerant of other agents or patients requiring TPA for CVC patency.…”
Section: Antibacterialsmentioning
confidence: 96%
“…26 Gentamicin 2.5 mg/mL with TSC 40 mg/mL remains stable, with no change in gentamicin concentration, for at least 112 days at room temperature. 5,7,8 Solutions of gentamicin 3 mg/mL and daptomycin 1 mg/mL with or without TSC 28 mg/ mL maintained more than 90% of the original drug concentrations for 48 hours. 9 Gentamicin 5 mg/mL has also been studied with EDTA 30 mg/mL, and visual compatibility for at least 72 hours at 25 or 37 °C was demonstrated.…”
Section: Antibacterialsmentioning
confidence: 99%
See 1 more Smart Citation
“…The antibiotic lock solution was prepared by either the inpatient pharmacy or an affiliated home infusion pharmacy under sterile conditions (22,23). The locking solution was instilled in a volume sufficient to fill each catheter lumen at the end of dialysis and aspirated at the next dialysis session before connection.…”
Section: Catheter Locking Solutionsmentioning
confidence: 99%
“…Based on previously published literature, incompatibility was defined as the presence of haze, particulate formation, gas evolution, color change, or precipitation on visual inspection, ≥1 pH unit change over the 4-hour course of the experiment, or any absorbance of >0.01 A. [7][8][9][10][11][23][24][25] To simulate actual Y-site infusion, we sought to replicate the infusion process conducted by nursing personnel in the clinical setting. All actual Y-site infusions were completed in duplicate to enhance the validity and accuracy of this study.…”
Section: Methodsmentioning
confidence: 99%